Internship and Monograph reports entitled”An Overview of Exosomes in Cancer Therapy: A Small Solution to a Big Problem" - Rodrigues, Paulo Miguel Rua (2020)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia